Mapping QTL for Seed Germinability under Low Temperature Using a New High-Density Genetic Map of Rice - Jiang, Ningfei; Shi, Shilai; Shi, Huan; Khanzada, Hira; Wassan, Ghulam M.; Zhu, Changlan; Peng, Xiaosong; Yu, Qiuying; Chen, Xiaorong; He, Xiaopeng; Fu, Junru; Hu, Lifang; et al. (Frontiers in Plant Science, 2017)
Mapping major quantitative trait loci (QTL) responsible for rice seed germinability under low temperature (GULT) can provide valuable gene sources for cold tolerant rice lines breeding. In this study, 124 rice backcross recombinant inbred lines (BRILs) derived from indica cv. Changhui 891 and japonica cv. 02428 were genotyped through re-sequencing technology, and a bin map including 3057 bins spanning 1266.5 cM with an average resolution of 0.41 cM between markers was generated. Based on the new high-density genetic map, six QTL ranged from 40 kb to 140 kb in Nipponbare genome were fine-mapped. Among these, qCGR8 and qGRR11, whose 02428 alleles could increase GULT and seed germination recovery rate after cold stress, respectively, were detected. qNGR1 and qNGR4 may be two major QTL affecting indica Changhui 891 germination under normal condition. qGRR1 and qGRR8 are two QTL affecting the seed germination recovery rate after cold stress, the Changhui 891 alleles can improve seed germination rate after cold stress dramatically. These QTL would be a highly valuable genetic factor for cold tolerant rice lines breeding. Moreover, the BRILs developed in this study serve as an excellent system for mapping and studying genetic basis of rice complex traits.